A Comparative Analysis of Wordwall-Based Anagram and Find-the-Match Media on Arabic Vocabulary Acquisition and Speaking Skills - Tanjung, Ferdian; Aunurrahman, Aunurrahman; Salam, Urai; Sujaini, Herry; Yani, Ahmad; Nur Halisah, Atikah; Xiaxanith, Toby (Universitas Islam Negeri Raden Intan Lampung, 2026)
The limited Arabic vocabulary mastery and low speaking ability of students indicate the need for instructional media that can enhance engagement and facilitate more effective language learning. This study aims to analyze the comparative effectiveness of Wordwall-based Anagram and Find-the-Match media on students’ Arabic vocabulary mastery and speaking skills. This study uses a quasi-experimental method with a nonequivalent control group design. The research employed a quantitative approach with a comparative design involving fifth-grade students at As-Salam Elementary School in Pontianak. Data were collected through vocabulary and speaking skill assessments administered after the implementation of both media. The obtained data were analyzed to identify differences in learning outcomes between the two instructional treatments. The research instruments included Arabic speaking skills tests that assessed fluency, pronunciation, vocabulary, and courage. The results showed that the experimental class experienced a higher average increase than the control class in all aspects of speaking skills. The average posttest scores of the experimental class for the aspects of fluency, pronunciation, vocabulary, and courage reached 82.2, 82.4, 85.1, and 86.4, respectively, while the control class only reached 71.8, 70.3, 67.5, and 74. This proves that the Wordwall anagram media is effective in improving students' vocabulary mastery and Arabic speaking skills. The implication of this study is that Arabic teachers are advised to utilize interactive digital media such as Wordwall as an innovative alternative in learning, as it has been proven to significantly improve students' motivation, vocabulary mastery, and speaking skills.